Digital Versus Conventional Impressions in Fixed Prosthodontics: A Review. Issue 1 (2nd August 2016) - Ahlholm, Pekka; Sipilä, Kirsi; Vallittu, Pekka; Jakonen, Minna; Kotiranta, Ulla
Abstract: Purpose: To conduct a systematic review to evaluate the evidence of possible benefits and accuracy of digital impression techniques vs. conventional impression techniques. Materials and Methods: Reports of digital impression techniques versus conventional impression techniques were systematically searched for in the following databases: Cochrane Central Register of Controlled Trials, PubMed, and Web of Science. A combination of controlled vocabulary, free‐text words, and well‐defined inclusion and exclusion criteria guided the search. Results: Digital impression accuracy is at the same level as conventional impression methods in fabrication of crowns and short fixed dental prostheses (FDPs). For fabrication of implant‐supported crowns and FDPs, digital impression accuracy is clinically acceptable. In full‐arch impressions, conventional impression methods resulted in better accuracy compared to digital impressions. Conclusions: Digital impression techniques are a clinically acceptable alternative to conventional impression methods in fabrication of crowns and short FDPs. For fabrication of implant‐supported crowns and FDPs, digital impression systems also result in clinically acceptable fit. Digital impression techniques are faster and can shorten the operation time. Based on this study, the conventional impression technique is still recommended for full‐arch impressions.